2018
DOI: 10.1101/453274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strongyloides stercoralis: spatial distribution of a highly prevalent and ubiquitous soil-transmitted helminth in Cambodia

Abstract: 14Background 15 Strongyloides stercoralis is a neglected soil-transmitted helminth that occurs worldwide and 16 can cause long-lasting and potentially fatal infections due to its ability to replicate within its 17 host. S. stercoralis causes gastrointestinal and dermatological morbidity. The objective of this 18 study was to assess the S. stercoralis infection risk, and using geostatistical models, to predict 19 its geographical distribution in Cambodia. 20 Methodology / Principal Findings 21A nation-wide comm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Studies on S. stercoralis epidemiology from Southeast Asia indicate that S. stercoralis infection are predominately found in men, that the infection increases with age and that rural populations have a higher risk for infection [ 7 , 8 , 10 , 14 ]. Our S. stercoralis patients follow these typical risk patterns although they have been recruited from a health services and not as the previous indicated studies from the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on S. stercoralis epidemiology from Southeast Asia indicate that S. stercoralis infection are predominately found in men, that the infection increases with age and that rural populations have a higher risk for infection [ 7 , 8 , 10 , 14 ]. Our S. stercoralis patients follow these typical risk patterns although they have been recruited from a health services and not as the previous indicated studies from the community.…”
Section: Discussionmentioning
confidence: 99%
“…In recent effort to model global S. stercoralis prevalence, an S. stercoralis infection prevalence between 10 and 15% has been estimated in Southeast Asian countries [ 2 ]. But a nation-wide survey in Cambodia detected a overall prevalence of 30.5% in the rural population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study, the detection of S. stercoralis larvae is part of a bigger schistosomiasis and STHs mapping which uses an AFRO questionnaire capturing data on schistosomiasis and STHs, thus the environmental variables and other potential risk factors for S. stercoralis such as walking barefooted, open defaecation, playing without shoes and eating fruits and vegetables that are not well washed within the two districts' school climate were not evaluated. Previous studies have reported that S. stercoralis infection is correlated with temperature, rainfall, open defaecation, inadequate portable water, farming, walking barefooted, playing without shoes, consuming fruits and vegetables which are not well washed ( Zeehaida et al, 2011 ; Kola et al, 2013 ; CDC, 2013 ; Beknazarova et al, 2016 ; Forrer et al, 2019 ). Differences between the two districts in socioeconomic demography, environmental factors and children's activities may explain our observations.…”
Section: Discussionmentioning
confidence: 99%
“…One main reason for this is the higher prevalence of infection in adults than children, owing to chronic infection, persisting indefinitely if not treated, as the consequence of the peculiar auto-infective cycle of the parasite. Although studies reporting data on age distribution of strongyloidiasis are scant [4][5][6][7][8], the higher prevalence in adults is biologically plausible, since in older ages we have a cumulative rate of strongyloidiasis owing to chronic and new infections that occur over time.…”
Section: Introductionmentioning
confidence: 99%